AB1201 INCREASING RATES OF INFLUENZA VACCINATION COVERAGE IN RHEUMATOID ARTHRITIS PATIENTS: DATA FROM A MULTICENTER, LONGITUDINAL COHORT STUDY OF 1, 406 PATIENTS. (2nd June 2020) - Thomas, K.; Lazarini, A.; Kaltsonoudis, E.; Drosos, A.; Repa, A.; Sidiropoulos, P.; Fragkiadaki, K.; Tektonidou, M.; Sfikakis, P.; Tsatsani, P.; Gazi, S.; Katsimbri, P.; et al.
Abstract : Background: Despite the increased incidence of influenza infection in rheumatoid arthritis (RA) patients, vaccination coverage has been shown to be suboptimal. Prospective data regarding the current rate and predictors of influenza vaccination adherence in RA patients are limited. Objectives: To calculate the current rate and predictors of influenza vaccination in a real-life, prospective, longitudinal RA cohort. Methods: Data regarding demographics, disease characteristics, treatments and co-morbidities from a multi-center, longitudinal cohort of Greek RA patients were collected at baseline and 3 years later. Disease and patient characteristics were compared between patients with at least one influenza vaccine administration and non-vaccinated ones, during the 3 year follow-up period. Results: From a cohort of 1, 569 RA patients, 1, 406 with available vaccination data at baseline and 3 years later (mean interval: 2.9 years) were included; (women: 80.4%, mean age: 61.8 years, mean disease duration: 9.7 years, RF and/or anti-CCP positive: 50.4%, mean DAS-28 = 3.33, mean HAQ: 0.44, bDMARD use: 44.8%). At baseline, 54.2% of patients reported influenza vaccination in the past (31.8% during the previous season), while during the 3 year follow-up period, 81% had ≥1 influenza vaccinations (p=<0.001). Patients who received ≥1 influenza vaccine were older (63.5 vs. 54.7 years, p<0.001), were more likely to be seropositive (59.2% vs. 45.2%, p<0.001), had higher HAQ (0.46 vs. 0.36, p=0.02) and BMI (27.7 vs. 26.9, p=0.02) at baseline, more likely to be treated with bDMARDs (46.8% vs. 36.4%, p<0.001) and more likely to have chronic lung disease (9.7% vs. 5.3%, p=0.02), dyslipidemia (36.4% vs. 24.2%, p<0.001), hypertension (46.1% vs. 29.2%, p<0.001) and to report vaccination against influenza the previous season before baseline evaluation (34.9% vs. 18.2%, p<0.001). By multivariate analysis, history of influenza vaccination during the last season before baseline (OR=1.87, CI: 1.27-2.74, p=0.001), bDMARD treatment (OR=1.51, CI: 1.07-2.13, p=0.018) and age (OR=1.05, CI: 1.04-1.06, p<0.001) were independent predictors of influenza vaccination. Conclusion: In this ongoing, longitudinal, prospective, real-life RA cohort study, a significant increase in the influenza vaccination coverage was noted (from 53% to 81%). Influenza vaccination was independently associated with recent history of influenza vaccination, older age, and bDMARD treatment. Acknowledgments: Supported by grants from the Greek Rheumatology Society and Professional Association of Rheumatologists. Disclosure of Interests: Konstantinos Thomas: None declared, Argyro Lazarini: None declared, Evripidis Kaltsonoudis: None declared, Alexandros Drosos: None declared, ARGYRO REPA: None declared, Prodromos Sidiropoulos: None declared, Kalliopi Fragkiadaki: None declared, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer, Petros Sfikakis Grant/research support from: Grant/research support from Abvie, Novartis, MSD, Actelion, Amgen, Pfizer, Janssen Pharmaceutical, UCB, Panagiota Tsatsani: None declared, Sousana Gazi: None declared, Pelagia Katsimbri: None declared, Dimitrios Boumpas: None declared, Evangelia Argyriou: None declared, Kyriaki Boki: None declared, Gerasimos Evangelatos: None declared, Alexios Iliopoulos: None declared, Konstantina Karagianni: None declared, Lazaros Sakkas: None declared, Konstantinos Melissaropoulos: None declared, Panagiotis Georgiou: None declared, Eleftheria Grika: None declared, PANAYIOTIS VLACHOYIANNOPOULOS: None declared, Theodoros Dimitroulas: None declared, Alexandros Garyfallos Grant/research support from: MSD, Aenorasis SA, Speakers bureau: MSD, Novartis, gsk, Constantinos Georganas: None declared, Periklis Vounotrypidis: None declared, Konstantinos Ntelis: None declared, Maria Areti: None declared, George D Kitas: None declared, Dimitrios Vassilopoulos: None declared